Pattern of Ocular Problems in School going Children of District Lasbela, Balochistan - P.S. Mahar, Khalil A. Lakho, M. Zahid Jadoon (Pakistan Journal of Ophthalmology, 2018)
Purpose: To find out the pattern of eye problems in children of age 6 to 15 years, attending schools and madaris (religious schools) and also to determine the difference in prevalence of ocular disease in students attending these different types of institutions. Material and Methods: The study was conducted in Madaris of district Lasbela were screened from February 2008 to September 2009. All students of schools / madaris of district Lasbela were included in the study. The visual acuity (VA) was measured using standard Snellen’s chart; external examination was carried out with the help of magnifying loop and direct ophthalmoscope. The children with VA < 6/12 were refracted to the best correction. The study team included a community ophthalmologist, an ophthalmologist, an ophthalmic technician and a community social worker. A structured questionnaire was prepared and operational methods were field tested and refined by piloting at the outpatient of Isra Postgraduate Institute of Ophthalmology, Al-Ibrahim Eye Hospital (AIEH), Karachi. An ophthalmic technician with community social worker checked vision of all the students and an Ophthalmologist examined the children for any abnormality and referred them to the base hospital (AIEH). All children with VA < 6/12 were refracted. Every school and madarsa of the target area was visited. Results: Out of 25,437 examined school going children, 19,629 (77.16%) were found to be normal while 5,808 (22.84%) had ocular problems. The ocular conditions in order of frequency were conjunctivitis in 2,826 (11.10%) children, vitamin A deficiency disorders in 839 (3.29%) children, refractive error in 740 (2.90%) children, vernal conjunctivitis in 484 (1.90%) children, blepheritis in 373 (1.46%) children, strabismus in 119 (0.46%) children, cataract in 45 (0.17%) children, ptosis in 33 (0.12) children, nystagmus in 26 (0.10%) children, glaucoma in 2 (0.007%) children and non-specific ocular changes were found in 259 (1.01%) children. The prevalence of ocular problems occurred in 20.68% of children in main stream schools compared to 34.33% in children studying in madaris. The main difference in prevalence was of conjunctivitis noticed in 10.03% of school children, compared to 17% of madaris students and of refractive error present in 2.14% of school children, compared to 7% of students in madaris. Conclusion: Almost 23% of school going children in Lasbela district needed treatment for their ocular problems. The prevalence of conjunctivitis and refractive error was more in madaris compared to schools. School screening could play an important role in the promotion of eye health and the prevention of childhood blindness.